Uma metodologia com uso de criptografia para ensino de funções - Carvalho, Valdemar Danilo de (Universidade Federal de São Carlos, 2020)
One of the biggest difficulties faced by teachers, nowadays, is the lack of interest from students in math’s programmatic contentes, wich, plenty of times, is reduced to a set of techniques, rules and algorithms without applicability or justification. This research’s objective is to investigate and analyze some possible contributions to mathematical functions’ teach-leraning using, as methodological approach, the resolution of math problems/ investigation utilizing a treasure hunt game, relating mathematical functions theory to the idea of cryptography, wich is part of the students’ routine.
A methodology using cryptography for teaching functions
Keywords: Aprendizagem; Funções; Criptografia; Ensino; Learning; Functions; Cryptography; Teaching; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO